Factors improving the utility of antiviral therapy for chronic hepatitis B: A nationwide multicenter study in Japan. Issue 13 (1st August 2018) - Yamagiwa, Yoko; Masaki, Naohiko
Abstract : Aim: The consideration of patients' needs in terms of research outcomes is emphasized in research promotion to eradicate hepatitis B virus according to the Basic Act on Hepatitis Measures in Japan. This study analyzed patients' attitudes toward experienced antiviral therapies for chronic hepatitis B and their need for future therapies. Methods: A self‐administered questionnaire comprising 124 questions was completed among patients with chronic hepatitis B from 61 core‐center hospitals designated to implement and research policies on hepatitis in 47 prefectures from August 2013 to January 2014 ( n = 3021, response rate = 51%). Results: In decision‐tree models with 333 variables generated from the questionnaire data, patients' satisfaction with therapy and reduction in anxiety about therapy were dependent on favorable therapeutic effects, sufficient information provided by the physician, and fewer lifestyle disturbances. Medical expenses were not selected at a superior branch because subsidy for antiviral therapy started in 2010. In correspondence analysis of free text answers, patients' need for therapy and support mechanisms differed among their attributes, including a great need for novel therapy in older men, hope for avoidance of lifestyle disturbance in younger men, and alleviation of painful experience with the disease in women. Conclusions: Continual provision of sufficient information is necessary to improve the utility of antiviral therapy for chronic hepatitis B as well as for favorable therapeutic effects. The patients believed that novel drugs and support would reduce the diverse burden of the disease on their lives.